Supporting student mental health while enhancing self-care: Evaluating the efficacy of a Graduate Teaching Assistant training module - Kristen A. Archbell; Kristin M. Brown (To Improve the Academy, 2025)
Given the unique proximity and approachability of graduate teaching assistants (GTAs) to students, training GTAs to support student mental health is critical. However, GTAs play dual roles as educators and students, who face their own stress and mental health challenges. This study examined the efficacy of an online module for GTAs focused on how to offer support to students while considering their own self-care. Using an online survey, GTAs’ beliefs (feelings of preparedness, and sense of responsibility) and responses (supportive behaviors) to scenarios of students in distress were examined. Participants also completed a measure of self-care. Compared with a general sample of GTAs who had not participated in the module (n = 111), module participants (n = 42) had higher intentions, felt more responsibility, and felt more prepared to support students in distress. They also reported higher levels of self-care. This study shows training can not only be effective at enhancing GTAs’ ability to support undergraduate student mental health but also positively impact their own self-care.